Effects of Artemisia annua L. Essential Oil on Osteoclast Differentiation and Function Induced by RANKL. (7th April 2022) - Sun, Wen; Yang, Guangyue; Zhang, Fang; Feng, Chenguo; Liang, Mingjie; Jia, Pengfei; Zhao, Zhongliang; Guo, Hailing; Zhao, Yongfang
Abstract : Objective . This study aimed to assess the main components of Artemisia annua L. essential oil (AEO) and determine their effect on the proliferation and differentiation of RAW264.7 cells induced by receptor activator for nuclear factor-ligand (RANKL) in vitro. Then, we tried to explain part of the function of its possible mechanisms. Materials and Methods . Essential oil was extracted from Artemisia annua L. Osteoclasts were induced in vitro by RANKL in mouse RAW264.7 cells. The experimental group was treated with different concentrations of AEO, while the control group was not treated with AEO. CCK8 was used to detect osteoclast proliferation. The osteoclasts were stained with TRAP. Western blot was used to detect protein in the MAPK pathway and the NF- κ B pathway after treatment with different concentrations of AEO. RT-PCR was used to determine the expression of osteoclast-related mRNA in cells. Results . The GC-MS analysis was used to obtain the main components of AEO, including camphor, borneol, camphor, borneol, terpinen-4-ol, p-cymene, eucalyptol, deoxyartemisinin, and artemisia ketone. The CCK8 results showed that the AEO volume ratio of 1 : 4000, 1 : 5000, and 1 : 6000 did not affect the proliferation of RAW264.7 cells. However, TRAP staining showed that AEO decreased osteoclast formation. Western blot results showed that the expression of protein TRAF6, p-p38, p-ERK, p-p65, and NFATc1 decreased in the MAPK pathway and the NF- κ B pathway affected by AEO. Furthermore, RT-PCR results showed that the expression of osteoclast resorption-related mRNAs (MMP-9, DC-STAMP, TRAP, and CTSK) and osteoclast differentiation-related mRNAs (OSCAR, NFATc1, c-Src, and c-Fos) also decreased in the experimental group. Conclusions . AEO inhibits osteoclast differentiation in vitro, probably by reducing TRAF6 activation, acting on the MAPK pathway and NF- κ B pathway, and inhibiting the expression of osteoclast-related genes.